Income Tax and Work Incentives: A Literature Review - Muslim, Muslim (Advances in Taxation Research, 2023)
Purpose: This study explores the impact of income tax policies, particularly progressive taxation, on labor market behavior, career development, and human capital formation across different economic contexts. It aims to analyze the effects of tax policies on work incentives in developed and developing economies, focusing on high-income earners, informal labor markets, and non-monetary factors such as job satisfaction and work-life balance. Research Design and Methodology: The research adopts a qualitative systematic literature review (SLR) methodology, synthesizing previous studies on the relationship between income tax policies and work incentives. The study compares the effects of taxation across income groups and economic environments, drawing insights from theoretical models and empirical findings. Findings and Discussion: The findings reveal that progressive taxation can reduce labor participation, particularly among high-income earners, while middle- and low-income workers are less affected. In developing economies, sizeable informal labor markets undermine the effectiveness of tax policies. Additionally, non-monetary factors, such as job satisfaction, are crucial in shaping labor market responses to taxation. Implications: The study suggests that tax policies should be tailored to different economic contexts, incorporating tax incentives for education and skill development to promote long-term economic growth. Policymakers should consider non-monetary factors when designing tax policies to ensure better labor market participation and productivity.